2017
DOI: 10.1021/acs.inorgchem.7b00503
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of a Base-Stabilized Germanium(I) Dimer toward Group 9 Metal(I) Chloride and Dimanganese Decacarbonyl

Abstract: The reactivity of the 2-imino-5,6-methylenedioxylphenylgermanium(I) dimer toward group 9 metal(I) chloride and dimanganese decacarbonyl is described. [LGe:] (1, L = 2-imino-5,6-methylenedioxylphenyl) underwent a disproportionation reaction with 1.5 equiv of group 9 metal(I) chloride [MCl(cod)] (M = Rh, Ir) in toluene to afford a mixture of the group 9 metallogermylene-chlorometal(I) complexes [LGeμ-{M(cod)}Cl] (M = Rh (2), Ir (4)) and chlorogermylene-chlorometal(I) complexes [L(Cl)GeM(cod)Cl] (M = Rh (3), Ir (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Recently, So et al. also showed that N→Ge coordinated digermyne behaved as a σ donor toward [{M(cod)Cl} 2 ] (M=Ir, Rh) and dimanganese decacarbonyl [Mn 2 (CO) 10 ] …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, So et al. also showed that N→Ge coordinated digermyne behaved as a σ donor toward [{M(cod)Cl} 2 ] (M=Ir, Rh) and dimanganese decacarbonyl [Mn 2 (CO) 10 ] …”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1-3 and 7 were prepared according to reports in the literature, [10,12] and TEMPO and [Fe(CO) 5 ]w ere purchased from Sigma Aldrich. The 1 H, 13 Ca nd 119 Sn NMR spectra were recorded on aBruker Avance500 spectrometer at 300 Ki nC 6 D 6 .C hemical shifts (d)a re given in ppm and referenced to external Me 4 Si and Me 4 Sn. Elemental analyses were performed on an LECO-CHNS-932 analyser.I Rs pectra were recorded on aN icolet 6700 FTIR spectrometer by using as ingle-bounce silicon attenuated total reflectance (ATR) crystal (resolution 2cm À1 ).…”
Section: General Methodsmentioning
confidence: 99%
See 3 more Smart Citations